Trifunctional electrocatalysts based on feather-like NiCoP 3D architecture for hydrogen evolution, oxygen evolution, and urea oxidation reactions. Issue 1 (1st January 2023) - Yang, Liming; Ru, Feng; Shi, Jinzhuo; Yang, Tao; Guo, Chunyu; Chen, Yafeng; Wang, Enhui; Du, Zhentao; Chou, Kuo-Chih; Hou, Xinmei
Abstract: Finding efficient and versatile catalysts that can both produce clean energy H2 and treat wastewater is an important matter to solve energy shortages and wastewater pollution. Herein, a feather-like NiCoP supported on NF was synthesized via the two-step hydrothermal-phosphorization process. NiCoP/NF requires only overpotentials of 44 and 203 mV to reach 10 mA cm −2 for HER and OER in 1 M KOH, respectively. Besides, NiCoP/NF requires only 1.13 V (vs RHE) to achieve 10 mA cm −2 in 1 M KOH containing 0.33 M urea. DFT calculation shows that NiCoP exhibits enhanced DOS in the Fermi level attachment, which promotes charge transfer. Subsequently, the trifunctional NiCoP/NF, for overall water splitting, requires a lower potential of 1.48 V to gain 10 mA cm −2 in 1 M KOH. For urea electrolysis, NiCoP/NF requires just 1.36 V to drive 10 mA cm −2 in 1 M KOH with 0.33 M urea. This work provides extraordinary insights into electrolytic hydrogen production and wastewater treatment through simple preparative methods. The performance of the prepared catalyst is at a high level in non-noble metal.